The Influence Of Price, Promotion And Location On Consumer Loyalty At PT. Karya Sukses Maju Bersama - Salman Faris; Jansen Layoji; Rivandy Anggesti; Nasib Nasib (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study examines and analyzes the effect of price, promotion and location on consumer loyalty at PT. Karya Sukses Maju Bersama. The research method used in this study uses a quantitative research method with a type of quantitative descriptive research that is explanatory. This analysis method uses software tools from SPSS 25 to analyze the results of the calculations of tests, such as classical assumption testing and multiple linear regression. The population in this study are all customers of PT. Karya Sukses Maju Bersama. . The sampling technique in this study used accidental sampling. The number of non-probability samples is 100 consumers, namely by determining 10 customers for 10 days of research. The data analysis method used is multiple linear regression. The results of the f test research where the result is that F count > F table (18.825 > 2.70) and a significant 0.000 <0.05 indicates Price, Promotion and Location on Customer Loyalty at PT simultaneously. Successful Work Moving Forward Together. The results of the t test research where Price, Promotion and Location partially have a positive and significant effect on the valid price of Customer Loyalty at PT. Karya Sukses Maju Bersama. The results of the analysis of the coefficient of determination obtained an Adjusted R2 value of 0.148, meaning that the variation of the Price (X1), Promotion (X2) and Location (X3) variables on Customer Loyalty (Y) is 35.1%. In comparison, the remaining 64.9% is explained by other variables which were not used in this study.